Regulating Ionizing Radiation Based on Metrics for Evaluation of Regulatory Science Claims - A. Alan Moghissi; Richard Calderone; Furzan Azam; Teresa Nowak; Sarah Sheppard; Dennis K. McBride; Lisa Jaeger (SAGE Publishing, 2018)
This article attempts to reconcile differences within the relevant scientific community on the effect of exposure to low levels of ionizing radiation notably the applicability of linear nonthreshold (LNT) process at exposures below a certain limit. This article applies an updated version of Metrics for Evaluation of Regulatory Science Claims (MERSC) derived form Best Available Regulatory Science (BARS) to the arguments provided by the proponents and opponents of LNT. Based on BARS/MERSC, 3 categories of effects of exposure to ionizing radiation are identified. One category (designated as S) consists of reproducible and undisputed adverse effects. A second category (designated as U) consists of areas where the scientific evidence for potential adverse effects includes uncertainties. The scientific evidence in the U category leads to a threshold. In contrast, the scientific foundation of the third category (designated as P) is questionable, as the scientific evidence indicates that adverse effects of the exposure at this level are not only questionable but may be helpful. This article claims that the third area is the domain of policy makers including regulators. This article describes Jeffersonian Principle that categorizes the affected community into specialists, knowledgeable nonspecialists, and the general public. Based on Jeffersonian Principle, the relevant scientific information, particularly the U and P areas, must be translated into a language that at a minimum is understandable to the knowledgeable group. Once this process is completed, the policy makers including regulators may select exposure limits based on their judgment.